FRANSUZ TILI DARSIDA O’YINLARDAN FOYDALANISH («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the methods used in teaching foreign languages in the educational system, as well as various modern games and innovative methods.
Keywords: multimedia, modern pedagogical methods, rebus, critical thinking, self- assessment.